Fixed point theorem for Nonlinear θ-φ-contraction via w-distance - Mohamed Rossafi; Abdelkarim Kari (Department of Mathematics, Hasanuddin University, 2022)
This paper is aimed to the notion of θ-φ-contraction defined on a metric space with w-distance. Moreover, fixed point theorems are given in this framework. Some illustrative examples are provided to advocate the usability of our results.As an application, we prove the existence and uniqueness of a solution for the nonlinear Fredholm integral equations.